Trans-Paradigm of Ex-Khilafah Ideologists; Paradigm Changes Analysis of Ex-Khilafah Ideologists in Tapal Kuda - Humaidi, Rif'an; Mukaffan, Mukaffan; Imam, Mashur (Universitas Nurul Jadid, 2023)
This research is based on the gap between the theory of religious conflict and the reality of the religious transition paradigm currently. Media issues have warmed up again lately with some news about the policy of disbanding radical mass organizations. After the dissolution of Hizbut Tahrir Indonesia (HTI), the Islamic Defenders Front (FPI) stumbled on administrative problems. After it was disbanded, the all members and cadres of the organizations chose to change their religious paradigm. The transition process is the main focus of this research. Based on the general framework of the shifting paradigm theory, the sub-focus consists of how to anomaly, the Critique process untill form a new paradigm of ex- Khilafah ideologues. In order to further limit the study, the site raised is the former ideologue Khilafah of Tapal Kuda. All problems are studied qualitatively using a phenomenological approach. The important findings of this study can be divided into three parts. First, the anomaly of the ex- Khilafah ideologue. There are three forms of anomaly, namely socio-cultural anomaly, siyasa anomaly and tradition anomaly. Second, the Critique process of ex- Khilafah ideologues. Its scope are socio-cultural Critique and siyasa Critique. Third, his new paradigm. There are two patterns of paradigm for the former ideology of the Khilafah, namely there are those who continue to fight for the Khilafah and there are those who choose to continue their ideological struggle. The first group carried out the process of marhala tsaqif and taf'ul. This last group bases its religious views on the majority, namely the religious paradigm of NU and Pesantren.